(untitled) (Annals of Medical Research, 2023)
Aim: Our aim is to present the pregnancy and delivery cases that occurred with successful enzyme replacement therapy (ERT) in our female Gaucher patients, whom we have followed and treated for years. Materials and Methods: We tried to retrospectively evaluate and present 9 pregnancy and delivery events that occurred with successful ERT in 4 of our 32 Gaucher patients, whom we have been following up and treated for years in our clinic. Patient monitoring parameters include regular clinical, biological, and radiological evaluations. We checked our Gaucher’s disease (GD) patients regularly at regular intervals before and during pregnancy for their hemoglobin, platelet, leukocyte, ferritin, blood sugar and creatinine levels. Results: 4 of the 32 cases were children, age range (4-16 years), 16 women age range (22-68 years), 12 men age range (34-72 years). Four of our cases have not received treatment yet. 12 of the female cases are receiving regular ERT (3 months-14 years). Of the male cases, 9 were receiving ERT (3-9) and 3 were not taking medication. One of our cases gave birth to a total of 4 children, first twins and then two single children with an interval of 3 years. Two of our patients had two deliveries and one of our patients with both Gaucher and SLE disease gave birth. Pregnant patients came to check-ups more frequently during pregnancy and were followed up and treated with a multidisciplinary approach each time they came. The ERT treatments of the patients were increased during pregnancy as the patient gained weight, and the symptoms that increased during pregnancy were relieved by increasing the dose. Conclusion: As a result, in our study, we observed that there was a healthy and successful pregnancy and delivery with ERT, which was started at the appropriate time and given at the appropriate dose. Comprehensive studies involving more cases are required in this regard.